Characterization of polyvinylidene fluoride trifluoroethylene/zinc oxide quantum dots composite thin films for pyroelectric nanogenerator applications / Nurazlin Ahmad - Nurazlin , Ahmad (2023)
In the first part of this study, the copolymer P(VDF-TrFE) thin films prepared by sol-gel method were annealed in the range of Curie temperature up to the melting point [80 °C – 140 °C] to increase their crystallinity. A remnant polarization, Pr of 76.7 mCm-2, which gives a pyroelectric coefficient of 31 μCm-2K-1 and a figure of merit (FOM) FD of 86 μCm-2K-1 (1 kHz) was obtained for the sample annealed at 100 °C, where the phase was about to transit from ferroelectric to paraelectric. In the second part, a novel P(VDF-TrFE) / ZnO QDs nanocomposite films stabilized with organic ligands (TEA) were fabricated using a spin-coating technique with fillers composition; 0, 0.15, 0.25, 0.35 and 0.50 wt%. Particle size analysis with UV-Vis and TEM confirmed that the QDs size is in the range ~2.5 - 3 nm. Incorporation of 0.15 wt% ZnO QDs into copolymer achieved optimum ferroelectric, dielectric and pyroelectric properties which gives the highest value of remnant polarization (Pr = 10.02 μC/cm2), dielectric constant (εʹ = 13.9) and pyroelectric coefficient (49 μC/m2K). The significant enhancement of these properties is because of the morphological structure of P(VDF-TrFE) which demonstrates higher distribution of micelle-like crystallite and growth of elongated rod-like crystallite. Including ZnO QDs in the polymer matrix induces local dipole moment due to its polar character giving rise to spontaneous polarization. Further measurement of the ferroelectric hysteresis loop leads to energy storage density, Ue is 8.2 J/cm3 and from pyroelectric activity, energy harvesting Figure of merit (FOM), FE is 19.5 Jm-3K2 obtained at 1 kHz for 0.15 wt%. The polarization of the non-centrosymmetric crystal structure of ZnO interacts synergistically with the P(VDF-TrFE) polymer host which contributes to the increase in ferroelectric and pyroelectric properties up to 0.15 wt% composition. The addition of ZnO QDs of more than 0.25 wt% in P(VDF-TrFE) degrades the ferroelectric properties due to excessive leakage current density and the emergence of saturated agglomeration as micelle-like hole structure on the surface of Si substrate, which cause the energy harvesting and storage performance to deteriorate. The Thermally Stimulated Current (TSC) study was performed to investigate the molecular motions of the crystalline copolymer P(VDF-TrFE) and its polymer composite P(VDF-TrFE) / ZnO QDs. The TSC measurement mainly revealed three depolarization peaks, which are known as the β, α and Curie mode (ρ) peaks in P(VDF-TrFE). The TSC spectrum’s relaxation peaks revealed spontaneous polarization or a switching characteristic of P(VDF-TrFE) observed at a specific temperature of Tg and the Curie mode. The involvement of space charges injection at the polymer/semiconductor interface and molecular-ions deep traps during the poling process of TSC can result in the decomposition the of TSC spectrum with high activation energy at most relaxation peaks of P(VDF-TrFE) / ZnO QDs. The pyroelectric nanogenerator developed in this research can be exploited to robust its performance in energy storage and energy harvesting applications.